Early Detection of Allergy Symptoms in Children and Adolescents, Characteristics of Possible Pathogens, Pre-Treatment Prevention Measures (in Poland) - Lisiecka, Maria Zofia (International Journal of Child Health and Nutrition, 2024)
Background: The purpose of this study was to investigate the main allergens and signs of the onset of allergic diseases and explore methods of prevention that do not include medicines. Methods: Non-parametric statistical methods were used. A retrospective study was conducted, which included 270 case histories. The average age of the patients was 19 (12.5; 40.1) years, 127 (47%) were men and 143 (53%) were women. Clinical diagnoses, early symptoms, allergen spectrum, and treatment recommendations provided by doctors were analyzed. It was established that the early signs of allergic rhinitis and rhinoconjunctivitis are nasal congestion, runny nose, and lacrimation, and the onset of atopic dermatitis is -characterized by dry and itchy skin. Results: Allergy to triggers from one group was present in 136 (50.4%) patients, irritants from two groups – in 95 (35.2%) patients, and irritants from three groups – in 39 (14.4%) patients. Polish doctors advised patients to limit their exposure to allergens but did not give recommendations for concrete actions. Conclusion: The results of the study can be used to help in the identification of the most common symptoms of allergic diseases and allergens, which is vital for the early diagnosis of this pathology by clinicians.